The Influence of Human Resource Development and Employee Competence on Performance in Government Assistants at the South Jakarta City Administration Secretariat - Rizke Chairunnisa (Jurnal Syntax Admiration, 2023)
This research aims to analyze the influence of human resource development and employee competency together on the performance of Government Assistants at the South Jakarta Administrative City Secretariat. The hypotheses tested are: (1) there is an influence of human resource development on the performance of Government Assistants at the South Jakarta Administrative City Secretariat. (2) there is an influence of employee competency on the performance of Government Assistants at the South Jakarta Administrative City Secretariat. (3) there is an influence of developing human resources and employee competency together on the performance of Government Assistants at the South Jakarta Administrative City Secretariat. This research uses a quantitative approach with explanatory and associative research types. In this research, the sampling technique used was saturated sampling or census, where all members of the population were used as samples. The sample in this study consisted of 38 respondents. The data analysis technique uses the correlation coefficient analysis method, coefficient of determination analysis, partial significance test (t test), simultaneous significance test (F test), and simple and multiple regression analysis. From the research results, the following conclusions were obtained: First, the human resource development variable has a strong and significant influence on performance with a correlation coefficient value of 0.789 and a coefficient of determination (r²) value of 0.632. Second, the employee competency variable has a strong and significant influence on performance with a correlation coefficient value of 0.665 and a coefficient of determination (r²) value of 0.443. Third, the variables of human resource development and employee competency together have a strong and significant effect on performance. This can be seen from the correlation coefficient value of 0.797 and the coefficient of determination (R2) value of 0.635.